A tribute to Mulk Raj Anand - Hasan, Md. Mahmudul (Asiatic Society of Bangladesh, 2005)
After I had read his books Conversations in Bloomsbury (1981) and Letters on India (1942) in early 2004, I became very keen on knowing whether Mulk Raj Anand was still alive. I approached some postcolonial experts and found them equally in doubt about his survival or death, or about his exact whereabouts. Finally the news of his death at 8:30 in the morning on Tuesday 28 September 2004 ended all my curiosities, as it also buried my faint hope of meeting this literary colossus some time in the near future. He chose to spend his last days quietly in the remote Indian district of Pune (near Bombay), where he died of pneumonia in Jehangir Hospital. He is survived by his wife Shirin Vajifdar and by his daughter Sushila Anand.